POLITICAL IDENTITY IN THE 2024 ELECTIONS THROUGH SOCIAL MEDIA INSTAGRAM - Puspita, Tina; Setyawan, Aldo; Prayogi, Shandy Fitro; Lestari, Aghnia Dian (Ridwan Institute, 2024)
Social media has become a part of everyday life for people around the world, and the use of social media as a medium for information exchange has become an important part of political communication. This study aims to explore the political identity in the 2024 elections through social media Instagram. The study focuses on how political identities are shaped, communicated, and influenced via Instagram. This research uses a qualitative method by conducting interviews with informants and conducting observations through Instagram social media. This research contributes to the growing body of literature on digital political communication, highlighting the role of Instagram in the formation and expression of political identity, and offering practical implications for political campaigns and social media strategies in future elections.